The Effects of the Affordable Care Act Dependent Coverage Mandate on Parents' Labor Market Outcomes - Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2021)
We examine the labor market impacts of the Affordable Care Act dependent mandate (ACA-DM), which has significantly increased dependent children's health insurance coverage through parents' employer-sponsored health benefits. Using data from the American Community Survey, we find that the ACA-DM reduced parents' annual wages by about 2,600. However, the probability of employment and working hours only decreased marginally. The back-of-the-envelope calculation indicates that the magnitude of the estimated wage impact is similar to the increased insurance premium of a family plan due to the ACA-DM. These findings imply that a deadweight loss associated with the expansion of dependent health coverage is likely to be small as an increase in employers' labor costs is offset by a reduction in parents' wages without significant reductions in labor inputs.
Keywords: I18; J32; H51; 330; The Affordable Care Act dependent mandate; dependent health insurance coverage; parents' labor market outcomes; deadweight loss